2001
DOI: 10.1152/ajpgi.2001.281.3.g645
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine transporter in crypts compensates for loss of villus absorption in bovine cryptosporidiosis

Abstract: Cryptosporidium parvum infection represents a significant cause of diarrhea in humans and animals. We studied the effect of luminally applied glutamine and the PG synthesis inhibitor indomethacin on NaCl absorption from infected calf ileum in Ussing chambers. Infected ileum displayed a decrease in both mucosal surface area and NaCl absorption. Indomethacin and glutamine or its stable derivative alanyl-glutamine increased the net absorption of Na(+) in infected tissue in an additive manner and to a greater degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…In the present study, an apparent stoichiometric ratio of about 1:1 for sodium-glucose and glutamine-glucose cotransport has been estimated, which is in accordance with classical experiments in rabbit ileum but probably underestimates the true absorptive glutamine:sodium ratio; other studies have suggested that a ratio of 2:1 was closer to the actual transepithelial influxes (3,5,13,20,29). Indeed, glutamine transport across intestinal brush-border membrane is only partly sodium dependent (36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, an apparent stoichiometric ratio of about 1:1 for sodium-glucose and glutamine-glucose cotransport has been estimated, which is in accordance with classical experiments in rabbit ileum but probably underestimates the true absorptive glutamine:sodium ratio; other studies have suggested that a ratio of 2:1 was closer to the actual transepithelial influxes (3,5,13,20,29). Indeed, glutamine transport across intestinal brush-border membrane is only partly sodium dependent (36).…”
Section: Discussionsupporting
confidence: 91%
“…In these models, hypersecretion was induced by cholera toxin (1,24,37), cryptosporidiosis (2,5,10), rotavirus (33), or enteropathogenic Escherichia coli (29). In cholera-infected humans, glutamine in the presence of glucose reduced net water and sodium secretion to the same degree as glucose alone (41).…”
Section: Discussionmentioning
confidence: 99%
“…Because the major nutrient for this rapidly renewing epithelium is glutamine, it is not surprising that this provisionally essential amino acid becomes rate limiting for epithelial repair in malnourished individuals. The discovery that glutamine and its stable derivative, alanyl glutamine, drive not only epithelial repair but also electrogenic sodium absorption (even in the presence of villus damage) provides an attractive approach to ORNT (158)(159)(160)(161). Glutamine causes improvement that cannot be completely explained by enhanced fluid and Na absorption, and it seems to improve intestinal epithelial cell integrity and enhance tight junction function (162)(163)(164).…”
Section: Scientific Challenges That Remainmentioning
confidence: 99%
“…In animal models of Cryptosporidium and Rotavirus, glutamine has been shown to stimulate sodium reabsorption in the small intestine even in the context of bowel villous atrophy (Blikslager, 2001). …”
Section: Nutritional Rehabilitationmentioning
confidence: 99%